THE NATIONAL WORLDVIEW IN THE TRADITIONS OF RUSSIAN AND UZBEK CHILDREN’S LITERATURE - Muradova Xurshida Baxtiyorovna (Modern American Journals, 2026)
Children’s literature plays a crucial role in shaping cultural identity, moral consciousness, and social values in younger generations. This article examines the representation of the national worldview in the traditions of Russian and Uzbek children’s literature from a linguocultural and comparative perspective and analyzes how national worldviews are reflected through thematic structures, symbolic imagery, folklore motifs, character systems, and culturally marked linguistic units in both literary traditions. Special attention is given to the depiction of family values, attitudes toward nature, collective and individual identity, and ethical ideals. By comparing Russian and Uzbek children’s texts, the research identifies both universal elements of childhood representation and culturally specific models rooted in historical, social, and spiritual contexts.
Keywords: National worldview, children’s literature, Russian literature, Uzbek literature, linguocultural analysis, cultural identity, folklore motifs, moral values, comparative literature, cultural transmission.